Automated and disrupted mobilities: Insights from the New Zealand industry sector - Shammut M; Imran M (Elsevier Ltd, 2025)
This paper aims to understand the readiness of automated vehicles (AVs) technology in New Zealand (NZ) through the lens of the mobilities paradigm. Drawing on interviews with AVs industry participants, the findings are categorised into three interrelated themes: (1) hard infrastructure, (2) soft infrastructure, and (3) future infrastructure development. First, hard infrastructure highlights the complexities of urban environments and AVs difficulty in predicting road users' movements. Second, soft infrastructure reveals that connectivity standardisation could enhance AVs communication, yet coverage inconsistencies may disrupt AVs Over-The-Air (OTA) updates. The findings also show how the AVs industry is perceived as ‘owners’ of AVs personal user data, raising ethical concerns around monetisation and surveillance. Third, future infrastructure development could help facilitate AV deployment, particularly through greater collaboration between and across the tech-industry, government, ‘ethical hackers’, and the use of techniques like ‘network slicing’. This paper concludes that while achieving driving autonomy is complex, deploying AVs in limited urban settings (e.g., shuttle services) offers opportunities to incrementally learn from real-world conditions. Overall, this paper responds to controversial and underexplored questions around AVs data ownership, industry use of personal data, infrastructure resilience, and government-industry collaboration for AV-ready cities. This paper contributes to the mobilities paradigm by extending our understanding of the unintended technological consequences of AVs uptake, and offers context-specific insights for policymakers, urban planners, and the industry to better understand the barriers and opportunities towards AVs implementation in future cities.
Keywords: Automated vehicles; Cities; Artificial intelligence (AI); Smart infrastructure; Planning; New Zealand